Quality of hypertension care: An improvement initiative in two outpatient health care centers. Issue 3 (18th November 2018) - Yusupov, Eleanor; Krishnamachari, Bhuma; Rand, Sarah; Abdalla, Mirette; Zwibel, Hallie
Abstract: Rationale, aims, and objectives: Hypertension control is an important public health goal; however, significant barriers remain in primary care practice. Our objective was to identify areas for improvement in hypertension care and implement changes in management to improve outcomes. We also aimed to evaluate whether quality improvement influences physician attitudes towards and adherence to current hypertension guidelines. Method: We conducted a non‐experimental pre‐ vs post‐ design quality improvement study for ambulatory patients with a history of hypertension. Specific measures of hypertension care were assessed at baseline and 3 months post‐implementation of the quality improvement initiative. De‐identified data were collected from 100 charts, randomly selected from the practice's electronic medical records, and compared with a national sample of peer data. The Intervention was based on the American Academy of Family Physicians METRIC Performance Improvement module. This consisted of creating a computerized registry, system improvements to the electronic medical records, and peer education workshops on best practices. A 7‐item survey was completed by primary care physicians pre‐ and post‐intervention. Results: Improvement was demonstrated in several primary outcome measures: increased number of patients counselled on sodium intake ( P  = 0.005), physical activity ( P  = 0.001), alcohol consumption ( P  = 0.03), and weight reduction ( P  < 0.0001). Practice self‐assessment findings did not show a statistically significant change following the intervention. Conclusions: This quality improvement increased provider compliance with hypertension guidelines. However, more effort is required to modify physician practices for full compliance with the 2017 updated hypertension guidelines.